2016
DOI: 10.1186/s12889-016-2870-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in mainland china: a meta-analysis of published studies

Abstract: BackgroundMetabolic syndrome (MS) comprises a set of conditions that are risk factors for cardiovascular diseases and diabetes. Numerous epidemiological studies on MS have been conducted, but there has not been a systematic analysis of the prevalence of MS in the Chinese population. Therefore, the aim of this study was to estimate the pooled prevalence of MS among subjects in Mainland China.MethodsWe performed a systematic review by searching both English and Chinese literature databases. Random or fixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
206
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(246 citation statements)
references
References 43 publications
30
206
4
6
Order By: Relevance
“…As adopted in similar reviews [32, 33], we conducted a meta-analysis proportion to estimate the prevalence of MetS among Ghanaians with no established disease. Individual study prevalence and pooled estimates were assessed at 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…As adopted in similar reviews [32, 33], we conducted a meta-analysis proportion to estimate the prevalence of MetS among Ghanaians with no established disease. Individual study prevalence and pooled estimates were assessed at 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…12 In India 21 and Bangladesh 20 the prevalence of MetS is similarly high, especially ral and urban populations, showed a higher prevalence of MetS in females than males. 18 A study from 7 cities across South America showed a similar prevalence of MetS in males and females, with the total prevalence levels varying from 14% in Ecuador to 27% in Mexico. 22 Data from African studies show a range of prevalence levels that are comparable with data from the developed world, particularly for urban-dwelling South African women ( Table 3).…”
Section: Epidemiology Of Metabolic Syndromementioning
confidence: 98%
“…Overnutrition, coupled with a sedentary lifestyle, has made obesity and MS global epidemics. In China, a recent study revealed that the prevalence of MS in Chinese adults has reached as high as 24.5% (IDF criteria modified for waist), causing a huge social and economic burden . Identification of this syndrome, which can easily be diagnosed in clinical practice using defined thresholds, allows for earlier intervention in these high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%